The effects of seaweed-based pellet binders on growth performance, feed efficiency and carcass characteristics in broilers - Farah Nurshahida, M. S.; Nashrin Iszhan, Ishak; Nurlin, Abu Samah; Khairul Amri, Abdul Aziz; Nazikussabah, Zaharudin (Elsevier Ltd, 2021)
Good quality pellets may improve feed efficiency and animal growth performance. In this study, the effects of the addition of seaweed binders (Kappaphycus alvarzeii and Sargassum polycystum) on growth performance and feed efficiency in broiler chickens were examined. The physicochemical properties and physical test of formulated broiler chicken feed in addition of potent seaweeds as binder were also examined. K. alvarzeii and S. polycystum were evaluated as binding agents in pelleted diets for broiler chicken over a period of 35 days. The experimental design was randomized complete block with 8 treatment diets and 6 replications per treatment. Broiler chickens were weighed, and the feed intake were taken weekly to determine the growth performance and feed efficiency. Feed formulations for broiler chicken with both seaweeds’ inclusions at different dietary levels (2, 5 and 10 %) were prepared. The parameters measured were body weight, feed intake (FI), feed conversion ratio (FCR) and carcass measurements. Based on the physicochemical and physical test, pellet quality (PDI and hardness) was observed better in 5% S. polycystum diets, which reflected on better results of feed intake (FI) on birds. The results showed that broiler fed with 2 % of S. polycystum showed the highest body weight. Following this, carcass evaluation was conducted on day 36 to record any effects of seaweeds towards body parts of birds. Based on the results, this study showed that inclusion of both seaweeds in broiler’s diet has no significant effect on carcass traits.